Comparison of Laparoscopic and Open Ureterolithotomy in Impacted and Very Large Ureteral Stones - Bayar, Goksel; Tanriverdi, Orhan; Taskiran, Mehmet; Sariogullari, Umut; Acinikli, Hüseyin; Abdullayev, Elshad; Horasanli, Kaya; Miroglu, Cengiz (Urology Journal, 2014)
Abstract Purpose: To compare the efficacy of laparoscopic and open ureterolithotomy in patients withureteral stones. Materials and Methods: Patients who had undergone open or laparoscopic ureterolithotomy between 2001 and 2013 in our clinic were enrolled in the study.Ureterolithotomy was performed due to the following reasons: failure to position the patient for ureteroscopy,unreachable stone with ureteroscopy also use of balloon dilatation, high stone volume, and the need for removal of kidney stones at the same session.. The patients’ demographic data, the volume of the stones, the duration of the operation and the hospital stay, the amount of analgesics administered after the operation, and the need for another procedure were compared. Results: Of study subjects 32 patients had undergone open and 20 patients had undergone laparoscopic ureterolithotomy. When the two groups were compared, there was no statistically significant difference with regard to the mean age (44.5-44 years), the body mass index (26-24.7 kg/m²), the stone volume (420-580 mm³), the duration of operation (122-123 min), the need for anotherprocedure and complications. The mean amount of analgesics administered after the operation (3.6 and 1.81 doses, P = .02) and the mean hospital stay (6.1 and 2.9 days, P = .01) were significantly lower in the laparoscopic ureterolithotomy group. Conclusion: Laparoscopic ureterolithotomy is a good alternative with less need for analgesia and a shorter hospital stay when compared with open ureterolithotomy.